Quantum Lithography: Achieving Sub-Diffraction Resolution using N00N States and Multi-Photon Absorption - Mammadov, Elchin; John, Kerry; Langa, John (Journal of Tecnologia Quantica, 2026)
Classical optical lithography is fundamentally limited by the diffraction limit, restricting achievable resolution in nanoscale fabrication. Quantum lithography has been proposed as a solution by exploiting entangled photon states, particularly N00N states, which enable interference patterns with sub-wavelength spacing. This study aims to investigate the feasibility of achieving sub-diffraction resolution using N00N states combined with multi-photon absorption processes under realistic conditions. A theoretical–computational approach was employed, integrating quantum optical modeling with numerical simulations across varying photon numbers, absorption orders, and loss parameters. Spatial resolution, fringe visibility, and absorption efficiency were used as key performance metrics. The results indicate that N00N states achieve resolution scaling inversely with photon number, successfully surpassing the classical diffraction limit. However, increased photon number significantly reduces multi-photon absorption probability and makes the system more sensitive to loss and decoherence. These findings reveal a fundamental trade-off between resolution enhancement and detection feasibility. This study concludes that quantum lithography offers a powerful pathway for sub-diffraction patterning, but practical implementation requires optimization of photon number, absorption efficiency, and system robustness to environmental disturbances.